2004
DOI: 10.1023/b:bile.0000025889.25364.4b
|View full text |Cite
|
Sign up to set email alerts
|

Use of Zymomonas mobilis and Saccharomyces cerevisiae mixed with Kluyveromyces fragilis for improved ethanol production from Jerusalem artichoke tubers

Abstract: Jerusalem artichoke mashed tubers were fermented using single yeasts and a bacterium as well as mixed culture of microorganisms. Kluyveromyces fragilis, a yeast with an active inulinase, was used together with either a commercial distillery yeast, Saccharomyces cerevisiae, or the bacterium Zymomonas mobilis. After batch fermentation the best ethanol concentration of 0.48 g g(-1) for the mixed population and 0.46 g g(-1) for the single population can be obtained. The theoretical yield of the mixed cultures was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(43 citation statements)
references
References 8 publications
2
40
0
1
Order By: Relevance
“…It showed that glucose with concentration above 150 g¨L´1 limits efficiency of bacteria of ethanol production, and over 220-230 g¨L´1 decreases total amount of produced ethanol (Figure 7). These results are consistent with the data measured by Nowak et al [33] and Szambelan et al [34]. They showed that glucose with concentration over 240 g¨L´1 inhibits the growth of cells of Z. mobilis (strain 3881).…”
Section: Screening the Ethanol Productivity Of Bacteriasupporting
confidence: 93%
“…It showed that glucose with concentration above 150 g¨L´1 limits efficiency of bacteria of ethanol production, and over 220-230 g¨L´1 decreases total amount of produced ethanol (Figure 7). These results are consistent with the data measured by Nowak et al [33] and Szambelan et al [34]. They showed that glucose with concentration over 240 g¨L´1 inhibits the growth of cells of Z. mobilis (strain 3881).…”
Section: Screening the Ethanol Productivity Of Bacteriasupporting
confidence: 93%
“…Jerusalem artichoke has been accepted as a good raw material for ethanol production, human diet and medical applications (Kaur and Gupta, 2002;Szambelan et al, 2004;Takeuchi and Nagashima, 2011;Chen et al, 2013;Jin et al, 2013), because the tuber is rich in fructose and inuline (Baldini et al, 2004;Saengthongpinit and Saijaanantakul, 2005). More importantly, Jerusalem artichoke has been utilized to exploit abandoned saline land in coastal zone in China at present due to its high salinity tolerance (Zhao et al, 2006;Xue and Liu, 2008;Long et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As it is abundantly available in nature and having fructose as its major composition, therefore it is suitable to be used as a substrate for fructo-oligosaccharides and high fructose syrup production for food, drink and pharmaceutical industries [4]. Moreover, fructose is also used as a substrate for bioethanol fermentation as renewable energy source by Saccharomyces cerevisiae and Zymomonas mobilis [5].…”
Section: Introductionmentioning
confidence: 99%